Breaking Barriers: The Influence of Teachers' Attitudes on Inclusive Education for Students with Mild Learning Disabilities (MLDs) - Mahwish Kamran; Sohni Siddiqui; Muhammad Shahnawaz Adil (MDPI AG, 2023)
Inclusive educational practices demand social justice where all students with special educational needs have the same right to access education, irrespective of their special needs. Increasingly, across the world, teachers are supporting and defending the inclusion of students with disabilities in mainstream schools and classrooms. This is also the case in Pakistan, the site of this study. However, support and defense are not assurance that such policy is accepted by classroom teachers. Previous research studies have identified some barriers to inclusion and in this regard, the attitudes of teachers have been identified as a barrier worthy of consideration. The present research can contribute to developing insights by suggesting all the factors that can accommodate students with mild learning disabilities (MLDs). The research study aimed to determine the attitudes of teachers towards the education of students with mild learning disabilities, which are due to hereditary and neurobiological reasons that alter the functioning of the brain by affecting one or more intellectual processes associated with learning. The problems of processing can interfere with basic skills of learning, such as reading, writing, and mathematical skills. They can also interfere with higher-order skills, such as organizational skills, abstract reasoning skills, thinking skills, long or short-term memory, and attention span, in an inclusive classroom setting. Using a quantitative research method, data were gathered from N = 230 sample cases of teachers selected through a stratified sampling technique from 10 private primary inclusive schools and 10 private primary non-inclusive schools in Karachi. To identify the attitudes of teachers towards the inclusion of students with MLDs, teachers were asked to respond to validated and reliable tools used in different studies. The research applied variance-based structural equation modeling using the partial least-squares modeling method. Smart PLS 3.0 is software used for variance-based structural equation modeling, and the purpose of using it that the model involves mediation. This tool can show direct and indirect associations among variables simultaneously. The results revealed that there is a weak linear relationship between teachers' attitudes towards the education of students with a mild learning disability and their practices towards inclusive classroom settings. On the contrary, teachers' positive attitudes towards mild learning disabilities are predictors of inclusive classroom settings in schools. The weak linear association between teachers' attitudes and the provision of inclusive classroom settings showed that teachers are not prepared to accommodate mild learning disabilities. However, if teachers' self-efficacy is increased, then teachers are prepared to accommodate mild learning disabilities. It indicates that teachers with a greater sense of self-efficacy can play a significant role in creating an inclusive environment in schools by employing the provision of relevant resources. The present study recommended certain support mechanisms to school management and provided guiding principles to them on the specific resources required to meet the needs of students with a mild learning disability and to increase the self-efficacy of teachers.